An Analysis of Surface Charging of Satellite in Orbit - Murugan, Sharvina; Anuar, Abul Khair (Evolution in Electrical and Electronic Engineering, 2025)
The Spacecraft Plasma Interaction Software (SPIS) has been employed to perform surface charging analysis of a generic GEO satellite in orbit. This study focuses on investigating the surface charging behaviour of a spacecraft under varying space plasma conditions, with particular emphasis on comparing Single Maxwellian and Bi-Maxwellian plasma distributions and analysing the effect of photoemission across various conductive surface materials. For each distribution type, simulation are carried out under both normal and worst-case plasma conditions to examine the extent of surface potential buildup. In addition, the effects of enabling and disabling photoemission which represent the presence and absence of Sun (eclipse) are analysed to understand their role in mitigating or exacerbating spacecraft charging. This study provides insight into how different plasma environments and emission mechanisms influence charging behavious on spacecraft surfaces.